(untitled) (Scientific journal of the Fergana State University, 2023)
The article analyzes issues such as the lexical-semantic nature of synonymous and contradictory words used in the stories of the famous writer Isajon Sultan, the importance of synonyms and antonyms in the process of linguistic analysis of a literary text.